2022
DOI: 10.3390/su14031358
|View full text |Cite
|
Sign up to set email alerts
|

The Places–People Exercise: Understanding Spatial Patterns and the Formation Mechanism for Urban Commercial Fitness Space in Changchun City, China

Abstract: The fitness industry is rapidly developing due to the demand for fitness activities, and a large number of commercial fitness spaces have emerged in Changchun city. The distribution of commercial fitness spaces in the city is not chaotic; different types of fitness spaces should have different spaces to choose from. The purpose of this article is to summarize the spatial distribution characteristics and laws of urban commercial fitness spaces, to help better develop commercial fitness spaces. Using Changchun (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Yi and Horton [13] proposed that China has abundant open green spaces and residential parks whose potential value for fitness and sports has not been fully explored, and that effective integration of the quantity and quality of garden green belts, residential green spaces, and sports fields can promote the future level of utilization of green space resources in China. In addition, other scholars have studied public fitness venues from the perspectives of their social attributes [14], spatial distribution [15,16], and accessibility [17]. By studying the spatial distribution of gymnasiums in Germany, Wu et al [18] found that the main factor affecting residents' satisfaction with fitness venues is accessibility, followed by conditions such as fresh air and clean environment.…”
Section: Introductionmentioning
confidence: 99%
“…Yi and Horton [13] proposed that China has abundant open green spaces and residential parks whose potential value for fitness and sports has not been fully explored, and that effective integration of the quantity and quality of garden green belts, residential green spaces, and sports fields can promote the future level of utilization of green space resources in China. In addition, other scholars have studied public fitness venues from the perspectives of their social attributes [14], spatial distribution [15,16], and accessibility [17]. By studying the spatial distribution of gymnasiums in Germany, Wu et al [18] found that the main factor affecting residents' satisfaction with fitness venues is accessibility, followed by conditions such as fresh air and clean environment.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the spatial distributions of sports parks in China, as well as the corresponding influencing factors, have been investigated by using different methods ( Table 1 ), including grid dimension analysis, spatial autocorrelation analysis, and kernel density estimation [ 17 , 18 ]. Indeed, the service capability of sports parks is closely related to their accessibility in a positive manner [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Some scholars have taken a fitness population perspective, and more related studies have focused on the differences in the fitness behaviors of different populations, such as the elderly, children, men, women, the rich, and the poor [10][11][12][13][14]. From the perspective of fitness venues, relevant research has paid greater attention to the transport range, accessibility, distribution characteristics, utilization rate, carrying capacity, and other influencing factors of these locations [15][16][17][18][19][20]. Some geographers are more concerned with the changes in fitness spaces within cities, and they usually considered elements, such as land use, neighborhood environment, accessibility, and population density, as the main factors influencing the changes in the fitness space [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%